Aromanians in the representation of Russian society of the second half of the 19th — early 20th centuries - Maksim Medovarov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The milestones in the formation of the image of Aromanians (Kutsovlakhs, Tsintsars) in the consciousness of the Russian public in ethnocultural, religious and political terms are considered. The gradual introduction of this topic into the agenda of pan-Slavic and Slavophile-minded diplomats, journalists, ethnographers is demonstrated, as well as attempts by foreign authors to influence public opinion in Russia in this regard. The sources include materials from periodicals (“Slavyanskie Izvestia”, “Novoe Vremya”, “Moskovskie Vedomosti”, etc.), ethnographic studies (A.S. Ionin, A.F. Rittich), travel essays (A.V. Amphiteatrov, P.A. Rittich, J. Lavrin, etc.). The works of Bulgarian and Serbian authors about the Aromanians published in Russia (S. Bobchev, S. Gopсeviс, S. Verkoviс, J. Cvijiс) are taken into account. The article examines ideas about the ethnogenesis of the Aromanians that existed in Russia at the end of the 19th – beginning of the 20th centuries, assessments of their way of life and national character, their relationships with the Greeks, Albanians, Slavs, and the Turkish authorities. A gradual shift has been noted from ideas about deeply Hellenized Vlachs to interest in their national awakening and the beginning of their struggle against the Patriarchate of Constantinople for church and linguistic autonomy in the Ottoman Empire. The reaction of Russian publicists to the Greek-Romanian conflict of the mid-1900s, its causes and consequences, to the further aggravation of the Aromanian issue under the rule of the Young Turks is analyzed. Attention is paid to the perception in Russia of the role of the Vlachs in the Balkan Wars and the Bulgarian-Romanian conflict of 1913, which changed the international status of the Aromanian question.